Analisis Pendapatan Pedagang Air Akar di Kecamatan Tampan Kota Pekanbaru - Haris Suryanegara; Eri Sayamar; Cepriadi ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to analyze the income of Root Water trader at Tampan Subdistrict, Pekanbaru City. Root Water is a traditional healthy drink from West Sumatera. This is the first research that talks about Root Water at Agribusiness Major, Agricultural Faculty, Riau University. Method which is used at this research is census method. The amount of respondent on this research are 21 traders. Business scale of this research is categorized as micro-scale business, as the number of employee that is participated on this business is only one or two participant per single operational day. None of the business owner at this research went bankrupt. According to the result of this research, the number of average net profit (advantage) from root water trader at Tampan Subdistrict Pekanbaru City is Rp.3.591.390,-. Keywords: Analytics, Income, Pekanbaru, Root Water, Tampan Subdistrict